Avaliação dos efeitos dos constituintes de óleos essenciais (timol, carvacrol e p-cimeno) na inflamação pulmonar aguda induzida por instilação de LPS em camundongos - Guerreiro, Marina Pinheiro [UNIFESP] (2015)
The acute respiratory distress syndrome (ARDS) is characterized by a diffuse inflammatory response, due to activation of pro-inflammatory agents and oxidants. Despite the high mortality, which affects 40% of patients, there are no specific therapeutic tool for the treatment, which is still based in protective ventilation and in the treatment of the underlying disease and the use of corticosteroids. Extensive research and the elucidation of the mechanisms involved in compounds extracted from plants have been great scientific interest, since many biological effects are shown related to the treatment with medicinal pants. Aim: 1. To evaluate the effects of treatment with thymol, carvacrol and p-cymene, monoterpenes, derived from essential oils of Lippia gracillis e L. sidoides plants, in respiratory mechanics and pulmonary histopathology in an experimental model of acute lung injury (ALI); 2. To evaluate if the presence and/or the position of hydroxyl radical in the chemical structure interferes in the bioactivity of these compounds in the model studied. Methods: Male Balb/c mice received LPS or saline intratracheally. After 6 hours of instillation, animals were treated with thymol, carvacrol, p-cymene (doses of 10, 15 and 20 mg / kg intranasal), dexamethasone (5 mg / kg intraperitoneally) or vehicle. After 24 hours from the time of LPS instillation we evaluated: the respiratory mechanics; inflammatory cells in the bronchoalveolar lavage (Bhavnani and Ballow) and peripheral blood, and total protein levels and proinflammatory cytokines in BALF, isoprostane, NF-?B, and the amount of collagen fibers in the lung tissue. Results: We show first that 6 hours after instillation of LPS, the animals had increased pulmonary inflammation compared to the control, and that this response increased in 24 hours, however changes in lung mechanics occurred only in 24 hours. Then we determined by means of a dose response curve, that 20mg/Kg was the most effective dose for the reduction of neutrophils for the three compounds evaluated. We observed that treatment with the three components of essential oils improved the respiratory function, reduced the amount of inflammatory cells in peripheral blood and BALF. Moreover, these treatments reduced the total protein content, IL-8 and IL-6 in BALF, the amount of collagen fibers and in the positive area of isoprostane in lung tissue. The cytokine IL-1? was not reduced by p-cymene compound and none of the compounds altered the levels of TNF-?. Moreover, thymol and carvacrol significantly reduced expression of P-65-NF-?B in the lung. These results were similar to those obtained with treatment with dexamethasone. Conclusion: Thymol and Carvacrol showed anti-inflammatory effect in a model of ALI, reducing pro-inflammatory cytokines, oxidative stress and inhibiting the activation of p-65-NF-?B, suggesting that the position of the hydroxyl group in the chemical structure does not interfere with the biological effect in this experimental model. Although the p-cymene compound, which has no hydroxyl group in its chemical structure, has reduced lung inflammation and oxidative stress, the mechanisms involved were different from those observed in thymol and carvacrol, since it had no effect on the expression of NF -?B and levels of IL-1? in lung. Together our results suggest that these compounds have significant therapeutic interest to treat inflammatory lung diseases, particularly ARDS and further studies are needed to clarify the exactly mechanisms of action and the importance of the hydroxyl in its structure.